Design Thinking in Menu Development with A Focus on Food Visual Aesthetics: Influence on Consumer Foodstagramming Behavior - Melissa Adriana Susanto; Bambang Iskandriawan (Green Publisher Indonesia, 2026)
The rapid growth of the Food and Beverage (F&B) industry in Surabaya has cultivated a highly competitive landscape, where business success is no longer determined solely by taste but also by visual aesthetics capable of triggering digital interaction. This study aims to identify the food visual aesthetic elements most relevant to Generation Z and Millennials and analyze their influence on foodstagramming behavior on Instagram. Employing a mixed-methods approach with a sequential exploratory strategy, the first phase utilized the Design Thinking framework from Empathize to Prototype to explore visual preferences through in- depth interviews with 24 respondents. Qualitative findings identified five key elements: contrasting colors, highlighted textures, strategic tableware selection, functional garnishing, and compositional balance. These elements were then manifested into three innovative menu prototypes as visual stimuli. In the second phase, quantitative testing was conducted on 139 respondents using Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The results demonstrate that visual aesthetic perception has a positive and significant influence on sharing intentions (foodstagramming), with a path coefficient of 0.676. Furthermore, a ceiling effect phenomenon (zero variance) was observed in responses to the innovative prototypes, empirically confirming that the human- centered design intervention achieved a maximum consensus of satisfaction. This study concludes that visual aesthetics are not merely supplementary but serve as a strategic trigger for generating organic promotion through User Generated Content (UGC).